2012
DOI: 10.5115/acb.2012.45.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Expression and roles of NUPR1 in cholangiocarcinoma cells

Abstract: Nuclear protein-1 (NUPR1) is a small nuclear protein that is responsive to various stress stimuli. Although NUPR1 has been associated with cancer development, its expression and roles in cholangiocarcinoma have not yet been described. In the present study, we found that NUPR1 was over-expressed in human cholangiocarcinoma tissues, using immunohistochemistry. The role of NUPR1 in cholangiocarcinoma was examined by its specific siRNA. NUPR1 siRNA decreased proliferation, migration and invasion of human cholangio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…NUPR1-dependent effects also mediate resistance to anticancer drugs (Giroux et al, 2006;Palam et al, 2015;Tang et al, 2011), an important characteristic of this malignancy. We (Sandi et al, 2011;Vasseur et al, 2002b) and others (Emma et al, 2016;Guo et al, 2012;Kim et al, 2012;Li et al, 2017;Zeng et al, 2017) have shown that genetic inactivation of Nupr1 antagonizes the growth of tumors in several tissues, including pancreatic cancer (Sandi et al, 2011) thereby supporting a role for this protein as a promising therapeutic target for the development of therapies for pancreatic cancer. Congruently, using a comprehensive approach that combines biophysical, biochemical, computational, and biological methods for repurposing FDA approved drugs in the treatment of pancreatic cancer, we have recently identified that the phenothiazine derivative, trifluoperazine, mimics the effect of the genetic inactivation of NUPR1, revealing its anticancer properties (Neira et al, 2017).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…NUPR1-dependent effects also mediate resistance to anticancer drugs (Giroux et al, 2006;Palam et al, 2015;Tang et al, 2011), an important characteristic of this malignancy. We (Sandi et al, 2011;Vasseur et al, 2002b) and others (Emma et al, 2016;Guo et al, 2012;Kim et al, 2012;Li et al, 2017;Zeng et al, 2017) have shown that genetic inactivation of Nupr1 antagonizes the growth of tumors in several tissues, including pancreatic cancer (Sandi et al, 2011) thereby supporting a role for this protein as a promising therapeutic target for the development of therapies for pancreatic cancer. Congruently, using a comprehensive approach that combines biophysical, biochemical, computational, and biological methods for repurposing FDA approved drugs in the treatment of pancreatic cancer, we have recently identified that the phenothiazine derivative, trifluoperazine, mimics the effect of the genetic inactivation of NUPR1, revealing its anticancer properties (Neira et al, 2017).…”
Section: Introductionmentioning
confidence: 72%
“…Several empiric observations have shown that cancer cells undergo growth arrest or cell death after genetic inactivation of NUPR1 in vitro and in vivo (Emma et al, 2016;Guo et al, 2012;Kim et al, 2012;Li et al, 2017;Sandi et al, 2011;Vasseur et al, 2002b). However, to date, the mechanisms responsible for the biological consequences of its inactivation in cancer cells remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic diagnoses of CCA were performed at the Department of Pathology, Pusan National University Hospital. Tissues were deparaffinized, rehydrated, and washed using xylene, ethanol, and PBS, respectively, and then antigen retrieval was performed using the citrate buffer as previously described [21]. Endogenous peroxidase activity was inactivated with 3% hydrogen peroxide for 15min.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, NUPR1-dependent effects also mediate resistance to anticancer drugs (14)(15)(16). We previously showed that genetic inactivation of Nupr1 antagonizes the growth of pancreatic cancer (10,17), and other laboratories have also shown that genetic inactivation of Nupr1 stops the growth of hepatocarcinoma (18), non-small cell lung cancer (19), cholangiocarcinoma (20), glioblastoma (21), multiple myeloma (22)(23), and osteosarcoma (24), thereby supporting this protein's role as a promising therapeutic target for developing new cancer therapies.…”
Section: Introductionmentioning
confidence: 99%